2004
DOI: 10.1029/2003jd004201
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional simulations of inorganic aerosol distributions in east Asia during spring 2001

Abstract: [1] In this paper, aerosol composition and size distributions in east Asia are simulated using a comprehensive chemical transport model. Three-dimensional aerosol simulations for the TRACE-P and ACE-Asia periods are performed and used to help interpret actual observations. The regional chemical transport model, STEM-2K3, which includes the on-line gas-aerosol thermodynamic module SCAPE II, and explicitly considers chemical aging of dust, is used in the analysis. The model is found to represent many of the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 47 publications
(91 reference statements)
7
104
1
Order By: Relevance
“…In this experiment, the STEM-2K3 model included aerosols in four size bins (in diameter): 0.1-0.3 mm, 0.3-1.0 mm, 1.0-2.5 mm, and 2.5-10 mm [Tang et al, 2004]. Thirty photolysis frequencies required for the SAPRC-99 mechanism are explicitly treated online taking into account the influence of aerosols and clouds [Tang et al, 2003].…”
Section: A4 University Of Iowa Stem-2k3 Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, the STEM-2K3 model included aerosols in four size bins (in diameter): 0.1-0.3 mm, 0.3-1.0 mm, 1.0-2.5 mm, and 2.5-10 mm [Tang et al, 2004]. Thirty photolysis frequencies required for the SAPRC-99 mechanism are explicitly treated online taking into account the influence of aerosols and clouds [Tang et al, 2003].…”
Section: A4 University Of Iowa Stem-2k3 Modelmentioning
confidence: 99%
“…This model has been generalized to simulate regional air quality [Tang et al, 2003;Carmichael et al, 2003;Tang et al, 2004], and the latest version is used here. During the TexAQS II experiment, STEM-2K3 provided a multiscale forecast, including a primary domain with 60-km horizontal resolution covering the contiguous United States, and a nested 12-km domain covering Texas.…”
Section: A4 University Of Iowa Stem-2k3 Modelmentioning
confidence: 99%
“…Ito and Y. Feng: Role of dust alkalinity in acid mobilization of iron other hand, mineral dust aerosols originating from the Asian deserts may exhibit a strong buffering ability by neutralizing the acidic pollutants encountered during the long-range transport (Iwasaka et al, 1988;Carmichael, 1999, 2001;Tang et al, 2004). Recently, McNaughton et al (2008) and Fairlie et al (2009) have argued that dust does not acidify in the free troposphere generally.…”
mentioning
confidence: 99%
“…This discrepancy could show that emissions of NO X are not merely the source of dust nitrate. Previous studies repeatedly reported that the formations of particulate sulfate and nitrate on sea salt particles (Eriksson 1959;McInnes et al 1994) and dust particles enhanced the production of particulate sulfate and nitrate in the downstream atmosphere (Nishikawa et al 1991;Dentener 1996;Tang 2004). The sea is about 2-3 km from the tested area, which is where the particles could have originated from, and the wind could have induced the transportation.…”
Section: Source Of Chemical Constituents Of Dust Fallmentioning
confidence: 99%